Hibernation site requirements of bats in man-made hibernacula in a spatial context - de Boer, W. F; de Koppel, S. van; de Knegt, H. J; Dekker, J. J. A (Ecological applications, 2013)
Bat hibernacula selection depends on various spatial and nonspatial variables that differ widely between sites. However, previous studies have focused mainly on nonspatial variables. This research investigated factors that determined the abundance and species richness of hibernating bats in hibernation objects of the New Dutch Waterline, The Netherlands, and determined the relevant scales over which spatial factors operate using regression techniques and ecological-niche factor analyses. The effects of 32 predictor variables on several response variables, i.e., the total bat abundance, species richness, and abundance and presence of bat species, were investigated. Predictor variables were classified as internal variables (e.g., building size, climatic conditions, and human access) or external variables (e.g., ground and vegetation cover and land cover type) that were measured at different spatial scales to study the influence of the spatial context. The internal building variables (mainly the size of hibernacula and the number of hiding possibilities) affected the hibernating bat abundance and species richness. Climatic variables, such as changes in temperature and humidity, were less important. The hibernation site suitability was also influenced by spatial variables at a variety of scales, thereby indicating the importance of scale-dependent species-environment relationships. The absence of human use and public access enhanced hibernation site suitability, but the internal size-related variables had the greatest positive effect on hibernation site suitability. These results demonstrate the importance of considering the different spatial scales of the surrounding landscape to better understand habitat selection, and they offer directives to managers to optimize objects for hibernating bats and to improve management and bat conservation. The analyses have wider applications to other wildlife-habitat studies.